Answer:
tex]a^2 - 4b \\eq 2[/tex]
Explanation:
We are given that a and b are integers, then we need to show that
![a^2 - 4b \\eq 2](https://img.qammunity.org/2020/formulas/mathematics/college/rr41xcuee8s2m8nx2dzwrs5shj170qycw2.png)
Let
![a^2 - 4b = 2](https://img.qammunity.org/2020/formulas/mathematics/college/goaj5qbvhrtoneejtn71epmvqv7zkqlxnn.png)
If a is an even integer, then it can be written as
, then,
![a^2 - 4b = 2\\(2c)^2 - 4b =2\\4(c^2 -b) = 2\\(c^2 -b) =(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/college/g8ycpwu6n2exelsorzgo9sq6p00tmz5n9q.png)
RHS is a fraction but LHS can never be a fraction, thus it is impossible.
If a is an odd integer, then it can be written as
, then,
![a^2 - 4b = 2\\(2c+1)^2 - 4b =2\\4(c^2+c-b) = 2\\(c^2+c-b) =(1)/(4)](https://img.qammunity.org/2020/formulas/mathematics/college/yrmyotjux2vr6zathlngj76gg4iipmhmrg.png)
RHS is a fraction but LHS can never be a fraction, thus it is impossible.
Thus, our assumption was wrong and
.